2022
DOI: 10.3389/fpsyt.2022.832196
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Refugees With a Culturally Adapted Digital Intervention to Improve Sleep: A Randomized Controlled Pilot Trial

Abstract: Refugees are exposed to multiple stressors affecting their mental health. Given various barriers to mental healthcare in the arrival countries, innovative healthcare solutions are needed. One such solution could be to offer low-threshold treatments, for example by culturally adapting treatments, providing them in a scalable format, and addressing transdiagnostic symptoms. This pilot trial examined the feasibility, acceptance, and preliminary effectiveness of a culturally adapted digital sleep intervention for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 105 publications
0
14
0
Order By: Relevance
“…Furthermore, the identified interventions were at different stages of their evaluation process. We included two RCTs (Nickerson et al, 2019 ; Röhr et al, 2021 ) and two pilot RCTs (Lindegaard et al, 2021b ; Spanhel et al, 2022 ), three feasibility studies (Holmes et al, 2017 ; Lindegaard et al, 2021a , 2022 ), two qualitative studies on the development process (Burchert et al, 2019 ), and the cultural adaptation of interventions (Spanhel et al, 2019 ). Moreover, two peer-reviewed study protocols (Böge et al, 2020 ; Fischer et al, 2021 ) and three interventions without any published study reports were identified.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the identified interventions were at different stages of their evaluation process. We included two RCTs (Nickerson et al, 2019 ; Röhr et al, 2021 ) and two pilot RCTs (Lindegaard et al, 2021b ; Spanhel et al, 2022 ), three feasibility studies (Holmes et al, 2017 ; Lindegaard et al, 2021a , 2022 ), two qualitative studies on the development process (Burchert et al, 2019 ), and the cultural adaptation of interventions (Spanhel et al, 2019 ). Moreover, two peer-reviewed study protocols (Böge et al, 2020 ; Fischer et al, 2021 ) and three interventions without any published study reports were identified.…”
Section: Resultsmentioning
confidence: 99%
“…According to the respective stage of evaluation, different clinical and nonclinical outcomes were reported: Four of the identified study reports collected data on clinical outcomes and tested efficacy in the context of RCTs (Nickerson et al, 2019 ; Röhr et al, 2021 ) or pilot RCTs (Lindegaard et al, 2021b ; Spanhel et al, 2022 ). One of the included study protocols described a planned RCT on the efficacy of a stepped and collaborative care model including the smartphone-delivered intervention as one of several low-threshold stand-alone interventions (Böge et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations